No changes in seedling recruitment when terrestrial mammals are excluded in a partially defaunated Atlantic rainforest - Brocardo, Carlos R. [UNESP]; Zipparro, Valesca B. [UNESP]; Lima, Renato A. F. de; Guevara, Roger; Galetti, Mauro [UNESP] (Elsevier, 2013)
One of the most intriguing questions in ecology is how to identify which and how many species will be able to inhabit human-modified landscapes. Large-bodied mammals structure plant communities by trampling, herbivory, seed dispersal and predation, and their local extinction may have pervasive consequences in plant communities due to the breakdown of key interactions. Although much attention has been given to understanding the effects of defaunation on plant communities, information on the potential impacts on plant functional groups (seed dispersal, seed size and seedling leaves defense) inhabiting continuous forests after defaunation is scarce. We conducted mammal surveys (line transects and camera trapping) to determine the defaunation status of a continuous Atlantic forest in Brazil. Then, we evaluated the effects of defaunation on seedling diversity, richness and abundance of functional groups using 15 plot-pairs (each pair with one open and one exclusion plot) monitored over 36. months. We found that the studied area is partially defaunated because it exhibits high abundance of primates, while terrestrial mammals, such as large rodents and ungulates, are rare. We found no significant changes in either seedling richness and diversity or in the seedling composition of plant functional groups in response to mammal exclosure. Seedling mortality and recruitment were similar between plot types. Our findings suggest that at semi-defaunated areas, where arboreal species are still present, terrestrial mammals have low impacts on the plant community reassembly. © 2013 Elsevier Ltd.
Keywords: Atlantic forest; Defaunation; Herbivory; Seed dispersal; Seed predation; Tapirus; Tayassu; abundance; anthropogenic effect; arboreal species; habitat fragmentation; herbivory; mammal; mortality; plant community; rainforest; recruitment (population dynamics); seed dispersal; seed predation; seedling; Atlantic Forest; Brazil; Mammalia; Primates; Rodentia; Ungulata